Verbal Means of Persuasion in English Educational Video Discourse: a Communicative‑pragmatic Perspective - Malakhovska , Yaryna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article presents a systematic communicative‑pragmatic analysis of verbal means of persuasion in English educational video discourse, conceptualized as a multimodal, socially situated phenomenon with a distinct discursive organization. Insufficient attention to specifically linguistic means of influence in the educational context has drawn our focus to the study of verbal means of persuasion in English educational video discourse. Persuasiveness in educational communication is most often interpreted through teaching methodology, whereas it is precisely linguistic units that ensure engagement, regulate behavior, and enhance the effectiveness of communication. The aim of the article is to identify and systematize verbal means that actualize persuasive influence in teacher talk and to trace their communicative‑pragmatic functions in educational video contexts. Persuasion in this case is construed as a discursive strategy oriented toward shaping learners’ knowledge, skills, and behavioural patterns through the combination of explicit and implicit linguistic resources. The paper focuses on lexicogrammatical means that verbalize the speaker’s persuasive intentions: action words, imperative constructions, modalities, evaluative language, and intensifiers. Action words function as semantic triggers that activate learners’ cognitive activity and directly realize the teacher’s intention to change behaviour or promote knowledge acquisition. Imperative constructions, examined in canonical, polite, verbless, and embedded forms, operate as instructive signals that set expected patterns of pupil behaviour. Modality in the educational discourse is represented by three primary types – bouletic, deontic, and dynamic – each contributing to the expression of will, obligation/permission, and ability respectively.  In English educational video discourse, verbal means of persuasion actualize the speaker’s intentions both explicitly and implicitly to foster learners’ acquisition of knowledge and skills.